(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Since the Industrial Revolution, human economic activities have added a huge amount of Greenhouse Gases (GHGs) into the environment. The rise in environmental pollution, the global average temperature, and sea level now present an alarming situation all over the world, requiring action by all concerned. It is in this regard that the present work has been undertaken with a focus on identifying and examining the drivers for their influence on organizations’ green adoption and sustainable performance. Through random sampling, primary responses were obtained from the managers of 103 organizations based in India. The use of step-wise regression analysis on cross-sectional data yielded findings that establish a significant impact of three out of five drivers, namely organization characteristics, public policy, and technology characteristics, on green adoption by organizations. The results also support a positive and significant impact of green adoption on economic, social, as well as environmental performance of organizations. The practical suggestions outlined in the study can be used by organizations to adopt and promote green programs as a profitable endeavor for their sustainable growth in the future.